2016
DOI: 10.1039/c6ra02620f
|View full text |Cite
|
Sign up to set email alerts
|

Full alignment of dispersed colloidal nanorods by alternating electric fields

Abstract: The parallel alignment of an ensemble of colloidal nanorods may unleash their application as the optically anisotropic constituent in polarized fluorescent sheets or polarization-selective detectors. Here, we demonstrate that full alignment of colloidal CdSe/CdS nanorods in suspension can be achieved by applying AC electric fields. Alignment is monitored by the concurrent change of the optical transmission of the dispersion. By comparing the transmission measurements to a theoretical model encompassing both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…To exploit the linearly polarized emission from QREFs, semiconductor QRs must be unidirectionally aligned, and, therefore, a number of techniques have been explored to achieve the high‐quality alignment for QRs, recently . The electric field assisted alignment, the electro‐spinning technique, and the unidirectional stretching of polymer films embedded with QRs[5d] are among the most popular approaches. Yet another versatile approach is based on the photoalignment of the liquid crystal monomer (LCM) films with embedded QRs 3,4,8.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the linearly polarized emission from QREFs, semiconductor QRs must be unidirectionally aligned, and, therefore, a number of techniques have been explored to achieve the high‐quality alignment for QRs, recently . The electric field assisted alignment, the electro‐spinning technique, and the unidirectional stretching of polymer films embedded with QRs[5d] are among the most popular approaches. Yet another versatile approach is based on the photoalignment of the liquid crystal monomer (LCM) films with embedded QRs 3,4,8.…”
Section: Introductionmentioning
confidence: 99%
“…The electro-optic behavior of colloidal suspensions of nanorods (i.e. rod-like nanoparticles) that show liquidcrystalline phases has raised wide interest in recent years [1][2][3][4][5][6][7][8][9][10][11][12] from both fundamental and applied perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous suspensions of anisometric particles are well known for their strong electro-optic response [13][14][15][16][17][18][19], due to a combination of two factors: the strong coupling of the particle orientation with the applied electric field E, and the strong optical anisotropy of the nanoparticles, which is either intrinsic or related to their anisometric shape [9,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NRs can emit saturated colors and the absorption and emission from these CdSe/CdS nanorods are highly polarized [3]. We have recently shown that NRs can be aligned effectively by applying an electric field [4].…”
mentioning
confidence: 99%